2015
DOI: 10.3109/00016489.2015.1032434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic exposure to electromagnetic waves on the auditory system

Abstract: The histopathologic and immunohistochemical analysis showed neuronal degeneration signs, such as increased vacuolization in the cochlear nucleus, pyknotic cell appearance, and edema in the group exposed to the electromagnetic fields compared to the control group. The average latency of wave in the ABR was similar in both groups (p > 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The ACx is increasingly understood to be an integral part of the network of brain regions responsible for prediction, auditory perceptual decision‐making, and learning, which play vital roles in the perceptual processing of complex acoustic stimulus [King et al, 2018]. The bioeffects of RF‐EMR on the function of different organs, such as the hypothalamus [Dundar et al, 2009], hippocampus [Gupta et al, 2018], the ear canal [Akdag et al, 2018], cochlea [Yorgancilar et al, 2012; Zuo et al, 2015], and cochlear nuclei [Özgür et al, 2015], have been widely investigated. However, few studies have investigated the effects of RF‐EMR on the ACx.…”
Section: Introductionmentioning
confidence: 99%
“…The ACx is increasingly understood to be an integral part of the network of brain regions responsible for prediction, auditory perceptual decision‐making, and learning, which play vital roles in the perceptual processing of complex acoustic stimulus [King et al, 2018]. The bioeffects of RF‐EMR on the function of different organs, such as the hypothalamus [Dundar et al, 2009], hippocampus [Gupta et al, 2018], the ear canal [Akdag et al, 2018], cochlea [Yorgancilar et al, 2012; Zuo et al, 2015], and cochlear nuclei [Özgür et al, 2015], have been widely investigated. However, few studies have investigated the effects of RF‐EMR on the ACx.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining cochlear damage were made at the magnetic field frequency which corresponds to the GSM frequency (300 MHz–300 GHz) and apoptosis in cochlear cells and degeneration of the cochlear nucleus were detected. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 When the use of low-frequency magnetic field for therapeutic purposes has become discussed in recent years, whether the low dose magnetic field causes damage to cochlear cells has become a research subject. In our study, we examined the effect of very low dose (40 Hz) magnetic field on the cochlea, which is used as a therapeutic dose in the literatüre.…”
Section: Discussionmentioning
confidence: 99%
“…The health risks of a variety of electrical household appliances, transmission lines, cellular phones, microwave communications and broadcast transmitters have been reported during recent years. For instance, studies have shown that exposure to electromagnetic fields may result in the development of electrohypersensitivity [1], neuropsychiatric effects [2], damage to auditory systems [3], childhood leukemia [4], brain tumors [5] and many, as yet unknown, symptoms. On the positive side, there have also been a variety of treatments and therapeutic methods exploiting these electromagnetic fields.…”
Section: Introductionmentioning
confidence: 99%